The Golden Fleece and the Golden-Fleeced Ram: Testimony and Interpretation of Ancient Literary Sources - Paparinska, Vita (Literatūra, 2018)
[full article, abstract in English; abstract in Lithuanian] The Golden Fleece figures in Greek mythology as the objective of the voyage of the Argonauts. The incompatability of the object of the search with the effort invested in its acquisition has furthered discussion of the real meaning of the Golden Fleece, which has generally been accepted to be a metaphor since antiquity. Modernity, especially at the turn of the 19th and 20th centuries, has been productive and inventive in the decipherment attempts of the metaphor’s hidden meaning. A number of interpretation theories has been developed, which, though interesting and wellargumented, are sometimes highly divergent from the interpretation of the Golden Fleece in the ancient sources. A proper understanding of the original or close to original meaning of the metaphor of the Golden Fleece requires a scrupulous look at ancient Greek and Roman testimony, an